2020
DOI: 10.22541/au.159731296.66103880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Center-Level CABG and Valve Operative Outcomes and Volume-outcome Relationships in New York State

Abstract: Background: We analyzed center-level outcome correlations between valve surgery and coronary artery bypass graft (CABG) in New York (NY) State and how volume-outcome effect differ between case types. Methods: We used the 2014-2016 NY cardiac surgery outcomes report. Center-level observedto-expected (O/E) ratio for operative mortality provided risk-adjusted operative outcomes for isolated CABG and valve operations. Correlation coefficient characterized the concordance in center-level outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…While the authors report a positive correlation between mortality outcomes following CABG and valve surgery in the state of New York, the correlation is modest with a correlation coefficient of only 0.31 1 . As reported, our group previously examined center specific morbidity and mortality outcomes following CABG and valve surgery within 18 institutions in Virginia between 2008 and 2015 and found a weak correlation in terms of mortality with a correlation coefficient of .22 for aortic valve replacement and CABG as well as .26 for mitral valve replacement and CABG 2 .…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…While the authors report a positive correlation between mortality outcomes following CABG and valve surgery in the state of New York, the correlation is modest with a correlation coefficient of only 0.31 1 . As reported, our group previously examined center specific morbidity and mortality outcomes following CABG and valve surgery within 18 institutions in Virginia between 2008 and 2015 and found a weak correlation in terms of mortality with a correlation coefficient of .22 for aortic valve replacement and CABG as well as .26 for mitral valve replacement and CABG 2 .…”
mentioning
confidence: 91%
“…These centers had better than expected CABG outcomes and worse than expected valve outcomes 1 . There was no discordance identified in centers with better than expected valve outcomes 1 . They concluded that while good outcomes following valve surgery may translate to improved outcomes following CABG, the opposite may not be true.…”
mentioning
confidence: 97%
See 3 more Smart Citations